Laparoscopic nephrectomy outside gerota fascia and en bloc ligation of the renal hilum for management of inflammatory renal diseases - Ma,Liang (2018)
ABSTRACT Objectives This study aims to improve laparoscopic nephrectomy techniques for inflammatory renal diseases (IRD) and to reduce complications. Materials and Methods Thirty-three patients underwent laparoscopic nephrectomy for IRD, with a method of outside Gerota fascia dissection and en-bloc ligation and division of the renal pedicle. Operative time, blood loss, complications, analgesia requirement, post-operative recovery of intestinal function and hospital stay were recorded. The degrees of perinephric adhesion were classified based on the observation during operation and post-operative dissection of the specimen, and the association of different types of adhesion with the difficulty of the procedures was examined. Results Among 33 cases, three were converted to hand-assisted laparoscopy, and one was converted to open surgery. Mean operative time was 99.6±29.2min, and blood loss was 75.2±83.5 mL. Postoperative recovery time of intestinal function was 1.6±0.7 days and average hospital stay was 4.8±1.4 days. By classification and comparison of the perinephric adhesions, whether inflammation extending beyond Gerota fascia or involving renal hilum was found to be not only an important factor influencing the operative time and blood loss, but also the main reason for conversion to hand-assisted laparoscopy or open surgery. Conclusions In laparoscopic nephrectomy, outside Gerota fascia dissection of the kidney and en-bloc ligation of the renal pedicle using EndoGIA could reduce the difficulty of procedure and operative time, with satisfactory safety and reliability. Inflammation and adhesion extending beyond Gerota fascia or involving renal hilum is an important predictor of the difficulty related to laparoscopic nephrectomy for IRD.